Applied Geometry Optimization of an Innovative 3D‐Printed Wet‐Scrubber Nozzle with a Lattice Boltzmann Method. Issue 3 (5th February 2022) - Reinke, Felix; Hafen, Nicolas; Haussmann, Marc; Novosel, Michael; Krause, Mathias J.; Dittler, Achim
Abstract: In contrast to conventional dry separators, new types of wet scrubbers with innovative nozzle geometries are capable of separating submicron particles with comparatively low pressure drop. As those geometries can easily be adapted using 3D‐printing manufacturing, an applied geometry optimization can lead to a fast and cost‐efficient product development cycle. In this study, the lattice Boltzmann method is used to optimize the pressure drop associated with a novel nozzle design. Simulated pressure drop data are validated with experimentally determined ones. By replacing originally installed ellipsoid‐shaped bluff bodies with foil‐shaped structures according to the 4‐digit NACA‐series, an optimization approach regarding the resulting pressure drop is described. Abstract : A single‐phase CFD model with a lattice Boltzmann method of an innovative 3D‐printed wet‐scrubber nozzle is implemented to analyze and optimize its pressure drop. The numerical model is validated against experimental data. An optimization approach regarding the flow guidance and pressure drop of the nozzle as well as the impact on the product development cycle is presented.